2021
DOI: 10.1007/s40520-021-01903-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exergaming on wellbeing of residents in a nursing home: a single blinded intervention study

Abstract: Introduction To improve the quality of life in nursing homes, meaningful activities and social contact are indispensable. Exergames can play a role addressing these needs. Methods In a randomized single blinded controlled intervention study, we investigated the effect of playing exergames on general wellbeing, fun and on social interaction. Results Thirty-five residents participated: 18 residents took part in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Various physical activities such as yoga, balance games, strength training, fishing, boxing, tennis, football, bowling, beat sabre and skiing are available in serious games, so such games are able to provide transformational therapeutic interventions through computer‐based activity and provide benefit to older adults with pain. Observed therapeutic effects, such as relaxing, stretching and strengthening abdominal and back muscles, have been reported in a group of older adults that revealed significant pain reduction; however, of the nine studies, two (Janhunen et al., 2023; J‐Lyn, 2014) did not report the type of games they used and four provided no information on pain duration (Gunst et al., 2022; Janhunen et al., 2023; J‐Lyn, 2014; Monteiro et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various physical activities such as yoga, balance games, strength training, fishing, boxing, tennis, football, bowling, beat sabre and skiing are available in serious games, so such games are able to provide transformational therapeutic interventions through computer‐based activity and provide benefit to older adults with pain. Observed therapeutic effects, such as relaxing, stretching and strengthening abdominal and back muscles, have been reported in a group of older adults that revealed significant pain reduction; however, of the nine studies, two (Janhunen et al., 2023; J‐Lyn, 2014) did not report the type of games they used and four provided no information on pain duration (Gunst et al., 2022; Janhunen et al., 2023; J‐Lyn, 2014; Monteiro et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This meta‐analysis aimed to determine the efficacy of serious games for chronic pain management in older adults with the analyses indicating efficacy of the overall effect on pain reduction immediately after the intervention. The following interventions aiming to manage chronic pain were applied and tested: computer and Windows‐based applications (Beltran‐Alacreu et al., 2022; Ditchburn et al., 2020), Xbox 360 Kinect Sport (Gunst et al., 2022), Nintendo Wii (Monteiro et al., 2015; Zadro et al., 2019) and virtual reality exergames (Stamm et al., 2022; Yalfani et al., 2022). To the best of our knowledge, this is the first study examining the effectiveness of serious games for chronic pain management in older adults, although the interventions did not appear to significantly affect pain‐related disability and fear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies evaluated exergaming [ 58 ], music therapy [ 59 ], and animal-assisted therapy [ 60 ], but these studies did not meet the inclusion criteria for this review. More experimental studies are needed to develop and evaluate cost-effective and easy-to-administer non-pharmacological sleep interventions in older adults that are appropriate for the evolving digital social environment and tailored according to individual health status.…”
Section: Discussionmentioning
confidence: 99%
“…Among community-dwelling older individuals with or without specific diseases ( 32 ), studies have proved the therapeutic application of exergames in improving lower limb strength ( 33 ), gait speed ( 34 ), balance ( 35 ), and cognitive function ( 34 , 36 ). Few studies have evaluated the clinical effectiveness of exergames in LTCFs, and most outcomes of these studies pertained to health-related quality of life (HRQoL), cognition, and general functional status ( 37 39 ). Our team found that the handgrip strength (HGS) and walking speed of elderly individuals with sarcopenia living in care facilities improved significantly after 12 weeks of exergame-based progressive RT( 40 ).…”
Section: Introductionmentioning
confidence: 99%